RECOGNIZING THE ENTREPRENEURIAL OPPORTUNITIES: A COMMON OUTCOME OF AN ENTREPRENEURIAL MINDSET - Bernardus, Denny; Murwani, Fulgentius Danardana; Aji, Imanuel Deny Krisna; Padmawidjaja, Liestya; Jatiperwira, Stefan Yudana; Hitipeuw, Imanuel (Jurnal Aplikasi Manajemen, 2023)
Entrepreneurship is important for economic growth in Indonesia. Entrepreneurial opportunities are essential to maintain a business. This study is intended to explore how business teams recognize entrepreneurial opportunities as a common outcome of their entrepreneurial mindsets. Specifically, this study explores how business teams express their ideas for introducing innovative products in a marketplace where entrepreneurial opportunities underlie those ideas. This study used a qualitative descriptive approach to achieve a comprehensive summarization. A few business teams had already enrolled in the entrepreneurship course. Each business team was asked to report how the business team recognized entrepreneurial opportunities. Content analysis was used to analyze the business team reports. The business team reports were coded into main categories, which the main categories were then analyzed using manifest analysis. The results showed that the business teams recognized the entrepreneurial opportunities underlying their business ideas. Business ideas have several characteristics. This study has implications, limitations, and suggestions for future studies.